ADSORPSI ION LOGAM Cr(III) PADA SILIKA GEL DARI ABU SEKAM PADI TERMODIFIKASI LIGAN DIFENILKARBAZON (Si-DPZon) - Suminten, Ni Ketut; Sudiarta, I Wayan; Simpen, I Nengah (Jurnal Kimia (Journal of Chemistry), 2014)
The adsorption of Cr (III) using silica gel from rice husk ash modified with diphenilcharbazon ligand (Si-DPZon) was investigated.The aim of this study was to determine the optimum pH and contact time, the pattern of adsorption isotherm as well as the type of interaction between metal ion and the silica gel through sequential desorption. The result showed that the silica gel resulted has a surface acidity (Kal) of 0.1046 mmol/g and number of active sites of 17,9672 x 10 20 atoms/gram. The adsorption optimum pH is 3.0 with the optimum contact time of 30 minutes where the Cr(III) adsorbed is 24,5047 mg/g. The adsorption follows the Freundlich isotherm. Interaction that occurs between the Cr (III) and the Si-DPZon adsorbent is dominated by physical interaction.
Keywords: adsorption, silica gel, ligand of diphenilcharbazon, metal cation of Cr(III)